Utilization of the Maktabah Syamilah Application in Learning the Old Book at the Darul Ulum Islamic Boarding School of Jember - Saipul Wakit; Moh. Dasuki; Zaharuddin M; Margiyono Suyitno (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Portrait of learning activities at partner locations still using classic books written by previous Salaf scholars called the old book using the bandongan and sorogan methods. In the development of the 4.0 era, there are increasingly more innovations in media and learning technology, including the Matabah Samilah application. This application has capacity and a large number of books in it which can be used as learning references in Islamic boarding schools. However, partners have not been able to implement it because 1) lack of knowledge about using the old book application, 2) do not yet have application-based computer technology skills in learning activities, 3) and there is no old book library that supports the increase and development of knowledge at partner locations. The activity methods that will be used are training, workshops, tutorials, practice and micro teaching simulations. The results of community service are increased knowledge, skills and implementation of Maktabah Syamilah as a digital old book library. From the results of the post test carried out at the end of the activity, the results showed that around 82% had good knowledge and skills in using the application, while the results of the knowledge test were sufficient and about 28% were insufficient.